Pengaruh Kualitas Pelayanan, Harga, Citra Merek Terhadap Kepuasan Pelanggan Bengkel San Motor - Irene, Shelina Avrielle; Artina, Nyimas (MDP Student Conference, 2025)
AHASS San Motor Workshop is an official Honda workshop located in Palembang. This study aims to analyze the influence of service quality, price, and brand image on customer satisfaction, both individually and simultaneously. The research employed a questionnaire using a Likert scale, distributed to 150 respondents. The sampling technique used was purposive sampling, and the data were analyzed using SPSS 24 software. The partial test (t-test) results indicate that the variables of service quality, price, and brand image have a t-value greater than the t-table value (1.655), meaning each variable significantly affects customer satisfaction. Meanwhile, the simultaneous test (F-test) results show that the F-value is higher than the F-table value (2.43), indicating that these three variables collectively influence customer satisfaction. Additionally, the coefficient of determination test results reveal that service quality, price, and brand image explain 71.4% of customer satisfaction.